Prospects for tourism development in Zaporizhzhya region - Oveskov, O. V. (ТДАТУ, 2019)
The purpose of this article is to identify promising types of tourism that can be developed in Zaporizhzhya by using the results of SWOT analysis of the tourism industry in this region.
Keywords: tourism; resort and tourist activity; results of SWOT